Therapeutic Relational Connection in Telehealth: Concept Analysis - Lisa V Duffy; Rebecka Evans; Veronica Bennett; Joan Marie Hady; Priya Palaniappan (JMIR Publications, 2023)
Background Therapeutic relational connection (TRC) in telehealth is a new concept that refers to the intentional use of relationship connection between health care providers and their patients as both parties work toward a therapeutic aim. It has been demonstrated that TRC positively affects patient-centered outcomes including adherence, self-management, and satisfaction with care. What is not known are best practices for establishing TRC during telehealth visits. The rapid emergence of telehealth during the COVID-19 pandemic has identified a number of challenges. These challenges include lack of human contact, distance creating mistrust, the inability to rely on nonverbal communication, and a sense of depersonalization. Training for health care providers in these interpersonal communication skills needed to establish TRC during telehealth visits is needed. Objective This paper aims to explore the evolutionary concept of TRC in telehealth. The purpose of this paper is to provide a concept analysis of TRC during telehealth interactions between providers and patients through a comprehensive review of the existing published literature. Methods Rodgers' evolutionary concept analysis method was used to guide this study. PubMed, Embase, PsycINFO, and CINAHL were used to search for relevant publications. An integrative review strategy aided by Rayyan software was used to identify a final sample of 13 papers for analysis. Results The proposed definition of TRC in telehealth is the experience of a mutually responsive patient-provider relationship that is built on mutual respect and understanding and informed by cultural humility, presence, empathy, and the ability to effectively evaluate patient concerns to work toward a therapeutic aim. The key attributes of TRC in telehealth are the provider's ability to evaluate patient concerns, interpersonal communication, cultural humility, mutual trust and respect, presence, empathy, and building relationships. Clinical presence, proper environment, knowledge about the use of technology (both patient and provider), use of verbal and nonverbal communication, and knowledge about community and culture are important antecedents of TRC. Consequences of TRC include improved communication resulting in mutual respect and caring, adherence to follow-up recommendations, increased coping, collaborative decision-making, and satisfaction with care. Conclusions Telehealth visits necessitate alternative approaches to establishing TRC as compared to in-person clinic visits. With the rapid expansion of telehealth platforms and a heightened acceptance of the technology, there is a need to integrate knowledge and provide a clear conceptualization of TRC in telehealth as TRC has been demonstrated to result in positive patient-centered outcomes. Identifying the attributes and antecedents of TRC in telehealth allows us the opportunity to develop guidelines and educational interventions aimed at training health care providers in the skills needed to establish TRC during telehealth visits.